Tendencias en la mortalidad por neumonía en adultos en Chile, 2000-2016 - ARANCIBIA H, FRANCISCO; ANDINO S, PAULETTE; GUTIÉRREZ-ARIAS, RUVISTAY; PARRAGUEZ D, CAMILO; ASTORGA C, FELIPE; DE LA FUENTE L, ALICIA (Revista Chilena de Enfermedades Respiratorias, 2022)
Objective: To analyze and model changes in the pneumonia mortality trend in the population over 15 years old of Chile, between 2000 and 2016. Methods: Epidemiological study based on information from public databases of vital statistics of the Department of Health Statistics and Information (DEIS) and the National Institute of Statistics (INE) of the Ministry of Health (MINSAL) of Chile. The cases were identified by the codes ICD-10 J12-J18. We calculated age-standardized overall mortality, according to sex and age group. Joinpoint regression analysis was used to model mortality and estimate the annual percentage of change (APC) in rates and identify significant changes in trends. APC was used as a summary measure. Results: During the period studied, the pneumonia mortality rate in Chile decreased significantly by 61.9%. Mortality rate diminished from 56.3 deaths per 100,000 inhabitants in 2000 to 21.7 deaths per 100,000 inhabitants in 2016 with an APC of -4.2%, (p < 0.05). Almost 90% of the deceased were over 65 years old. Conclusions: Mortality rates for pneumonia in Chile in people over 15 years of age show a significant sustained decreasing trend in the period between 2000 and 2016.